Oil palm kernel shell concrete mix design and bond strength - Elmagarhe, Asad Mohamed (2012)
Malaysia has been known for years to produce more than half of the world's output of palm oil and produces approximately 3.13 million tonnes as wastes in the form of oil palm shells (PKS) every year. A multitude of efforts have been made in the direction of waste management, and one of these plans are the use of PKS as a lightweight aggregate that can be used for construction purposes. However, the properties of Lightweight OPS concrete depend on the mix proportions, type of sand and the physical properties of the materials used. In order to ensure that PKS concrete can be used for structural purposes the compressive strength should be at least 25 Mpa. The physical and mechanical properties of PKS concrete showed that the densities and the 28-day compressive strengths of the concrete vary in range from 1750-2050 kg/m3 and 12-24 N/mm2, respectively, which are not acceptable to be utilized in structural application. Therefore, this project focuses on strength performance of PKS concrete by finding optimized mix design as well as the bond strength between concrete and steel bars. This work started by choosing a suitable mix to be used for PKS concrete design. ACI 211.2-98 and ASTM C 330-00 have been chosen in order to start conducting trial mixes and to prepare the materials used in optimized mix design. Metakaolin has been used as a mineral admixture to ascertain its contribution in improving the properties of PKS concrete. Tests on the mechanical properties were conducted and the relationship between mechanical properties was analysed. PKS concrete containing 10% metakaolin showed a stronger bond and an increase of 28-day compressive strength by almost 25%. The splitting tensile strengths and modulus of rupture of PKS concrete were found to be 7% and 20% of their compressive strengths. The modulus of elasticity was found to be around 12KN/mm2 which is higher than values found in the previous studies. Higher experimental bond strengths were recorded for PKS concrete compared to predicted values and bond strengths were found to be approximately 18% and 9% of compressive strength for deformed and plain bars respectively.